Empirical essays on IPOS: the Brazilian case - Baptista, Ricardo Fuscaldi de Figueiredo (2011)
The purpose of this study is to empirically analyze the main factors that determine the first-day return and the Flipping activity in Brazilian IPOs, taking into account expected results according to national and international researches. The data base encompasses IPOs that took place between May 2004 and February 2011, summing up to 129 IPOs and approximately R$ 128 billion offering. The first-day return, which means the ‘money left on the table’, was on average 4.6% taking into consideration the issue price, while the Flipping activity totalized R$ 7.2 billion, meaning 5.6% of the offering. The first-day return was analyzed before and after the first trade, and evidences were found supporting (a) the exogenous determination of the issue price, (b) the opening price dependence of prospectus disclosure and of other variables, observable previously to the bookbuilding process, and (c) the cascade behavior of investors in the pricing after the first trade, particularly driven by the underwriter behavior. In regards to the Flipping, it was notorious depending on how much the IPO succeeded, being concentrated in and homogeneous along the first-day, despite the intense negotiation in the first minute. As a general contribution to literature, it was concluded that Information Asymmetry Theory arguments are not sufficient to explain the first-day Underpricing and the Flipping, being necessary arguments based on Behavioral Finance adapted to an intraday perspective.